Diagnosis and Treatment of Optic Nerve Trauma - Zimmerer, Rüdiger; Rana, Majeed; Schumann, Paul; Gellrich, Nils-Claudius (Facial Plastic Surgery, 2014)
Decreasing visual acuity secondary to orbital trauma or orbital and anterior skull base surgery may be caused by either sudden space-occupying intraorbital lesions, including retrobulbar hemorrhage (RBH), or direct damage to the prechiasmatic pathway. Contrary to traumatic optic neuropathy, RBH must be diagnosed and treated immediately to prevent permanent damage to the visual system. Therefore, monitoring and handling of visual pathway damage are mandatory. Flash visual evoked potentials and electroretinograms can provide evidence of the status of conductivity of the visual pathway when clinical assessment is not feasible. Both are thus essential diagnostic procedures not only for primary diagnosis but also for intraoperative evaluation. In case of RBH surgical decompression is compulsory. However, traumatic optic neuropathy does not respond to either corticosteroids or optic canal surgery. Modern craniomaxillofacial surgery requires detailed consideration of the diagnosis and treatment of traumatic visual pathway damage with the ultimate goal of preserving visual acuity.
Keywords: retrobulbar hematoma/hemorrhage; optic nerve decompression; traumatic optic neuropathy; TON; visual pathway damage; flash visual evoked potentials; VEPs